2018
DOI: 10.1007/s12011-018-1435-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated with High Levels of Aluminum, Arsenic, Cadmium, Lead, and Mercury in Hair Samples of Well-Nourished Thai Children in Bangkok and Perimeters

Abstract: Toxic element exposure increases risk of neurodevelopmental disorders. However, hair element profiles of well-nourished urban resident children were largely unknown. We identified prevalence and the contributing factors of high hair aluminum (Al), arsenic (As), cadmium (Cd), lead (Pb), and mercury (Hg) levels in 111 Thai children (aged 3-7 years old). Most participants were well-nourished with high socioeconomic status. Since ROC curve of hair element data showed inadequate sensitivity for cutoff set-up, US re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…There are no studies reporting data on these factors in Malagasy girls to the authors' best knowledge. Confirmed influence of both factors, nutritional status of the girls and place of residence on the accumulation in their hair studied elements is consistent with the previously cited studies that not only environmental pollution, but also the nutritional status and the quality of the diet used, affect the exposure of the human organism to toxic elements (59,66,69,76) . ANOVA analysis showed that neither nutritional status level expressed by Cole index (Factor A) nor place of residence (Factor B) affected the As, Ni, Pb, Sb or Sn concentration in hair samples of the studied girls (Table 4).…”
Section: Toxic Elements Accumulation In Relation To Nutritional Status and Environmental Exposuresupporting
confidence: 90%
See 3 more Smart Citations
“…There are no studies reporting data on these factors in Malagasy girls to the authors' best knowledge. Confirmed influence of both factors, nutritional status of the girls and place of residence on the accumulation in their hair studied elements is consistent with the previously cited studies that not only environmental pollution, but also the nutritional status and the quality of the diet used, affect the exposure of the human organism to toxic elements (59,66,69,76) . ANOVA analysis showed that neither nutritional status level expressed by Cole index (Factor A) nor place of residence (Factor B) affected the As, Ni, Pb, Sb or Sn concentration in hair samples of the studied girls (Table 4).…”
Section: Toxic Elements Accumulation In Relation To Nutritional Status and Environmental Exposuresupporting
confidence: 90%
“…There are no studies reporting data on these factors in Malagasy girls to the authors' best knowledge. Confirmed influence of both factors, nutritional status of the girls and place of residence on the accumulation in their hair studied elements are consistent with the previously cited studies that not only the environmental pollution but also the nutritional status and the quality of the diet used affect the exposure of the human organism to toxic elements (61,68,71,78) .…”
Section: Toxic Elements Accumulation In Relation To Nutritional Statu...supporting
confidence: 90%
See 2 more Smart Citations
“…At this stage of the research, authors may speculate only that a diet poor in protein and bioelements and a diet rich in grains increases the accumulation of REE in the bodies of malnourished children. This effect is observed for heavy metals, especially cadmium [ 30 , 31 , 32 , 33 ]. Malnourished Malagasy children did not consume meat, fish or milk (nutritional interview data).…”
Section: Resultsmentioning
confidence: 99%